(x+2) (x+3)+ (x-2) (x-3) - 2x (x+1) = 0
Answers
Answered by
1
Step-by-step explanation:
(x+2)(x+3)+(x-2)(x-3)-2x(x+1)=0
x(x+3)+2(x+3)+x(x-3)-2(x-3)-2x²-2x=0
x²+3x+2x+6+x²-3x-2x+6-2x²-2x=0
x²+x²-2x²+3x+2x-3x-2x-2x+6+6=0
12-2x=0
2x=12
x=12/2
x=6
Answered by
0
Answer:
1/6
Step-by-step explanation:
(x+2)(x+3)+(x-2)(x-3)-2x(x+1)=0
x²+5x+6+x²-5x+6-2x²-2x=0
12-2x=0
2(6x-1)=0
x=1/6
Similar questions
Chemistry,
5 months ago
Math,
5 months ago
Computer Science,
5 months ago
English,
11 months ago
Math,
11 months ago
Social Sciences,
1 year ago
English,
1 year ago